Effective elastic moduli of metal honeycombs manufactured using selective laser melting. Issue 5 (7th February 2020) - Hussein, Rafid; Anandan, Sudharshan; Spratt, Myranda; Newkirk, Joseph W.; Chandrashekhara, K.; Heath, Misak; Walker, Michael
Abstract : Purpose: Honeycomb cellular structures exhibit unique mechanical properties such as high specific strength, high specific stiffness, high energy absorption and good thermal and acoustic performance. This paper aims to use numerical modeling to investigate the effective elastic moduli, in-plane and out-of-plane, for thick-walled honeycombs manufactured using selective laser melting (SLM). Design/methodology/approach: Theoretical predictions were performed using homogenization on a sample scale domain equivalent to the as-manufactured dimensions. A Renishaw AM 250 machine was used to manufacture hexagonal honeycomb samples with wall thicknesses of 0.2 to 0.5 mm and a cell size of 3.97 mm using 304 L steel powder. The SLM-manufactured honeycombs and cylindrical test coupons were tested using flatwise and edgewise compression. Three-dimensional finite element and strain energy homogenization were conducted to determine the effective elastic properties, which were validated by the current experimental outcomes and compared to analytical models from the literature. Findings: Good agreement was found between the results of the effective Young's moduli ratios numerical modeling and experimental observations. In-plane effective elastic moduli were found to be more sensitive to geometrical irregularity compared to out-of-plane effective moduli, which was confirmed by the analytical models. Also, it was concluded that thick-walled SLM manufactured honeycombs have bending-dominated in-plane compressive behavior and a stretch-dominated out-of-plane compressive behavior, which matched well with the simulation and numerical models predictions. Originality/value: This work uses three-dimensional finite element and strain energy homogenization to evaluate the effective moduli of SLM manufactured honeycombs.